HLA‐DQ and ‐DR alleles in patients with SLE: A tertiary hospital‐based case–control study in Bangladesh. Issue 1 (24th February 2023) - Khan, Muhammad S. A.; Ahmed, Shamim; Bandhan, Iftekhar H.; Zaman, Farhana; Sajib, Md. Kamrul H.; Tarafder, Shirin; Choudhury, Minhaj R.; Haq, Syed A.; Zaman, Mohammad M.
Abstract: Background: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by the involvement of multiple organs and autoantibody production. This study aimed to determine the association of human leukocyte antigen (HLA)‐DQ and ‐DR alleles with SLE at a tertiary hospital in Bangladesh. Methods: This case–control study was conducted in the Department of Rheumatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. The patients who fulfilled the 1997 revised American College of Rheumatology classification criteria for SLE were considered cases ( n  = 41). The controls ( n  = 32) were selected from the hospital staff of BSMMU, including doctors and nurses who did not suffer from any known rheumatic diseases, and there was no such disease in their first‐degree relatives. Polymerase chain reaction using a sequence‐specific primer (PCR‐SSP) in a low‐resolution typing method was carried out on blood samples collected for HLA‐DQ and ‐DR allele typing. Results: The cases and controls had comparable mean ages (31 vs. 32 years), and most cases were female (95.1% vs. 34.4%). The most frequent clinical manifestations were mucocutaneous (85.4%), followed by musculoskeletal (70.7%) and constitutional symptoms (58.5%). The cases had a significantly higher frequency of HLA‐DR2 allele compared with healthy controls (70.7% vs. 43.8%; odds ratio: 3.1; 95% confidence interval: 1.2–8.2). In addition, HLA‐DQ6 allele was found to have a significant association with mucocutaneous manifestations of the cases (88.9%, P  = 0.03). Conclusions: Bangladeshi adults having HLA‐DR2 may be more susceptible to SLE. HLA‐DQ6 allele might be associated with mucocutaneous manifestations of SLE. Abstract : Association of HLA‐DQ and ‐DR alleles in patients with SLE in the Bangladeshi population Key points: HLA‐DR2 allele was found in patients with SLE in significantly higher frequency than the healthy Bangladeshi adults. HLA‐DQ6 allele was found to have a significant association with mucocutaneous manifestations of the cases. The first study in Bangladesh with HLA‐DQ alleles in patients with SLE. Limitations: Single tertiary level hospital‐based study and small sample size.